Relationship among Sex, Pattern of Weakness and Treatment Outcomes of Post-Stroke Patients: A Register-Based Longitudinal Study - Shaligram Chaudhary; Lok Raj Joshi; Bibek Koju (Journal of Lumbini Medical College, 2022)
Introduction: Differences in stroke care and health outcomes between males and females are debated globally. Sex differences in functional outcomes after stroke rehabilitation are poorly investigated in the context of Nepal. This study aimed to explore the relationship among patients’ sex, side of weakness, and post-stroke health outcomes after rehabilitation in a hilly western region of Nepal. Methods: A register-based longitudinal study was conducted in a rehabilitation center including all consecutive patients with stroke who came for rehabilitation ( ayurvedic, homeopathic, acupuncture, and physiotherapy ) from March 2018 to March 2020. Modified Rankin Scale score at a three-month follow-up after a visit to the center was the main outcome measure. It was reported using relative risk and 95% confidence intervals. Results: The study included 384 stroke patients, among them 241 (62.8%) were males. Right-sided weakness was 1.262 times (RR =1.262, 95% CI = 1.016-1.567) more likely in males than in females. Male stroke patients were 1.104 times more likely to achieve a good outcome than females (RR=1.104, 95% CI = 1.007-1.211) and these findings were statistically significant. There was no association between the side of weakness and the outcome. Conclusion: More males, compared to females, visited for rehabilitation and achieved a good outcome (mRS0-2) after three months. Right-sided weakness was more common in males than in females.